Bisexual identity concealment for marital harmony: cultural and religious pressures in Malaysia - Mohd Rafizey Dalin; Nur Hafizah Yusoff; Azlina Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the concealment of bisexual identity among married men in Malaysia, a country where homosexuality is both stigmatized and criminalized under Syariah law. The problem lies in the immense cultural, religious, and legal pressures that compel these men to hide their sexual orientation, leading to significant emotional and psychological challenges. The primary objective of this research is to explore how these men manage their bisexual identities while maintaining marital harmony within a conservative, heteronormative society. Using a qualitative phenomenological approach, in-depth interviews were conducted with 15 self-identified bisexual men married to heterosexual women. The data were analyzed through thematic analysis. The findings reveal that societal expectations, fear of divorce, and family reputation are key factors influencing their decision to hide their sexual orientation. Participants reported high levels of anxiety, guilt, and isolation due to the dual pressure of performing heteronormativity in public while concealing their true selves in private. This study contributes to understanding the challenges faced by bisexual men in mixed-orientation marriages in Malaysia, particularly the psychological toll of maintaining secrecy. The implications underscore the need for culturally sensitive mental health services and policy reforms to provide adequate support for bisexual individuals. Such interventions are critical to reducing stigma and promoting emotional well-being in conservative societies.